״Death Accrued, But Somehow I Continued Living״: On Response and Resistance in Shimon Adaf’s Works - Jean Baroukh, Rina (MiKAN, 2021)
In this article Baroukh illustrates two central complementary and recurring movements in Adaf’s writing, especially in his early work, and in the transition from one book to the next. These movements or actions are what Baroukh has termed "response" and "resistance." Together they complete a poetic transition. They are also an essential part of the writer’s task and the artist’s character, as defined by Adaf. Initially, these movements can be seen in the transition from Adaf’s first poetry book, Icarus’ Monologue, to his second, What I Thought Shadow Is the Real Body. Later these movements of response and resistance appear even more prominently in Adaf’s transition from poetry to prose. His first novel, One Mile and Two Days Before Sunset, perfectly embodies this concept. It combines the two movements together, both in the choice to write a detective novel, and through Adaf’s detective, Elish Ben Zaken. This character is based upon two literary models: The first is Eliah Ben Shafat, the biblical prophet, who represents the "response" and the other is Elisha Ben Avuya, the heretic or "the other, ״ who represents the "resistance."